Effect of SiO2 Nanoparticle in Low-Temperature Molten Salts as Heat Transfer Fluid for Heat Recovery System - Logharamana Subramaniam; Wan Muhammad, Wan Nur Azrina (Journal of Advanced Mechanical Engineering Applications, 2025)
The utilization of low-temperature molten salts as heat transfer fluids in heat recovery systems has gained significant attention due to their advantageous physical and thermal properties. The relatively low thermal conductivity of molten salts limits their overall efficiency in transferring heat. The objective of this research to study the characteristic and thermal properties of quaternary molten with addition of SIO2 nanoparticle. Quaternary molten salt mixture of substance are LiNO3, KNO3, Ca(NO3)2, NaNO3 with combination of nanoparticle, SiO2 were used. Thermo Gravimetric Analysis (TGA), Differential Scanning Calorimetry (DSC), Differential Thermal Analysis (DTA) and X-Ray Diffraction (XRD) testing were conducted. Based on the results and data discussion, the best composition of SiO2 nanoparticles in the quaternary molten salt for heat transfer fluid and heat storage was determined. Sample B exhibited the lowest melting point of 87.3?, sample B had the highest heat capacity of 1.6 J/K.g, and sample C demonstrated the best thermal stability with the lowest mass change of -0.538917mg. Therefore, it can be concluded that Sample B had the optimal composition of SiO2 in the quaternary molten salt, providing a low melting point and high heat capacity.